Pacific Asia in the 1990s - Shibusawa, Masahide (Routledge, 1992)
Pacific Asia is in a period of transition. The region has to adapt to the new post-Cold War era, maintain its enviable economic growth record and find an effective voice in world affairs. This book - a collaborative venture, combining the complementary viewpoints of a Japanese author, a Malaysian author and someone from outside the region - looks at the main economic and political trends among the Pacific Asian countries in the second half of the 1980s, and suggests where the potential problems - and opportunities - lie, not only for the coming decade but beyond. The authors examine the broad patterns of economic interdependence and security linkages both within the region and with external partners, then analyze in detail the political economy of the newly industrialised economies, the patterns of complementarity and competition in Southeast Asia, the dilemma of reform or retrenchment facing China and the smaller regional socialist states, and the paradoxes of Japan's attempts to define its role in the region and the world. This book should be of interest to lecturers and scholars of politics and international relations, economics, business and Japanese and Asian studies.